2014
DOI: 10.3835/plantgenome2013.10.0035
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐Assisted Backcrossing to Introgress Resistance to Fusarium Wilt Race 1 and Ascochyta Blight in C 214, an Elite Cultivar of Chickpea

Abstract: Fusarium wilt (FW) and Ascochyta blight (AB) are two major constraints to chickpea (Cicer arietinum L.) production. Therefore, two parallel marker-assisted backcrossing (MABC) programs by targeting foc1 locus and two quantitative trait loci (QTL) regions, ABQTL-I and ABQTL-II, were undertaken to introgress resistance to FW and AB, respectively, in C 214, an elite cultivar of chickpea. In the case of FW, foreground selection (FGS) was conducted with six markers (TR19, TA194, TAA60, GA16, TA110, and TS82) linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 48 publications
2
108
2
Order By: Relevance
“…The legume community has been successful in developing several molecular breeding products despite the late arrival of genomic resources and trait-associated markers (Varshney et al, 2013a,b;Pandey et al, 2016;Varshney, 2016). Some key examples include resistance to Fusarium wilt and ascochyta blight (Varshney et al, 2013b) and improved drought tolerance (Varshney et al, 2013a) in chickpea; resistance to nematode and high oleic acid (Chu et al, 2011), resistance to leaf rust , and resistance to high oleic acid (Janila et al, 2016) in groundnut; resistance to rust disease (Khanh et al, 2013), soybean mosaic virus (Saghai-Maroof et al, 2008;Shi et al, 2009;Parhe et al, 2017), and low phytate (Landau-Ellis and Pantalone, 2009) in soybean; Striga resistance and seed size in cowpea (Lucas et al, 2015; see Boukar et al, 2016); pyramid genes for resistance to ascochyta blight and anthracnose in lentil (Taran et al, 2003); powdery mildew resistance (Ghafoor and McPhee 2012), lodging resistance (Zhang et al, 2006), frost tolerance (see Tayeh et al, 2015b), and Aphanomyces root rot resistance (Lavaud et al, 2015) in pea; and resistance to common bacterial blight disease (Miklas et al, 2000(Miklas et al, , 2006Mutlu et al, 2005;O'Boyle and Kelly, 2007), rust and viruses (Stavely, 2000), rust, anthracnose, and angular leaf spot (Oliveira et al, 2008), rust (Feleiro et al, 2001), and anthracnose (Alzate-Marin et al, 1999) in common bean. Several of these improved lines have either been released or are in the release pipeline in different countries.…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%
“…The legume community has been successful in developing several molecular breeding products despite the late arrival of genomic resources and trait-associated markers (Varshney et al, 2013a,b;Pandey et al, 2016;Varshney, 2016). Some key examples include resistance to Fusarium wilt and ascochyta blight (Varshney et al, 2013b) and improved drought tolerance (Varshney et al, 2013a) in chickpea; resistance to nematode and high oleic acid (Chu et al, 2011), resistance to leaf rust , and resistance to high oleic acid (Janila et al, 2016) in groundnut; resistance to rust disease (Khanh et al, 2013), soybean mosaic virus (Saghai-Maroof et al, 2008;Shi et al, 2009;Parhe et al, 2017), and low phytate (Landau-Ellis and Pantalone, 2009) in soybean; Striga resistance and seed size in cowpea (Lucas et al, 2015; see Boukar et al, 2016); pyramid genes for resistance to ascochyta blight and anthracnose in lentil (Taran et al, 2003); powdery mildew resistance (Ghafoor and McPhee 2012), lodging resistance (Zhang et al, 2006), frost tolerance (see Tayeh et al, 2015b), and Aphanomyces root rot resistance (Lavaud et al, 2015) in pea; and resistance to common bacterial blight disease (Miklas et al, 2000(Miklas et al, , 2006Mutlu et al, 2005;O'Boyle and Kelly, 2007), rust and viruses (Stavely, 2000), rust, anthracnose, and angular leaf spot (Oliveira et al, 2008), rust (Feleiro et al, 2001), and anthracnose (Alzate-Marin et al, 1999) in common bean. Several of these improved lines have either been released or are in the release pipeline in different countries.…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%
“…The MABC has been successfully employed recently to introgress AB resistance with double-podding traits in chickpea cultivars CDC Xena, CDC Leader, and FLIP98-135C [110], and a QTL-hotspot containing QTLs for root traits and abiotic stress tolerance in JG 11, a leading chickpea cultivar from India [111]. Varshney et al [112] demonstrated the use of MABC to develop superior lines resistant to AB. To develop resistant lines, two QTL regions for AB, ABQTL-I and ABQTL-II, were targeted for introgression.…”
Section: Inheritance and Marker Assisted Breeding For Ab Resistancementioning
confidence: 99%
“…In addition to the foreground, back-ground selection was performed for selection of plants with high recurrent parent genome recovery, with evenly distributed 40 SSR markers. After three backcrosses and three rounds of selfing, 14 MAB lines were generated for AB [112]. Phenotyping of these lines has identified seven resistance lines for AB.…”
Section: Inheritance and Marker Assisted Breeding For Ab Resistancementioning
confidence: 99%
“…By using 2-3 rounds of backcrossing and selfing, BC 2 F 3 and BC 3 F 2 homozygous lines have been developed at ICRISAT. (Varshney et al, 2013c) Aschochyta blight resistance Back cross progenies from (C 214 × ILC 3279) (Varshney et al, 2013c) Drought tolerance Back cross progenies from (JG 11 × ICC 4958) (Varshney et al, 2013b) Back (Smith et al, 2010) Rust resistance Back cross lines (Khanh et al, 2013) Two major MABC projects are underway in chickpea at ICRISAT and its partner organizations. Under the Tropical Legume-I initiative of CGIAR Generation Challenge Programme in collaboration with Bill & Melinda Gates Foundation, significant efforts have been made to develop drought tolerant progenies (BC 3 F 3:4 ) in the genetic background of JG11, a leading variety in India, by transferring a genomic region, "QTLhotspot," that contains several QTLs for drought tolerance traits (Varshney et al, 2013b).…”
Section: Common Beanmentioning
confidence: 99%
“…In this initiative, efforts are being made to introgress resistance to different races independently as well as pyramiding of resistance to two races for FW in some elite varieties in India. ICRISAT (India) is pyramiding resistances for Foc1 and Foc3 from WR 315 and 2 QTLs for Ascochyta blight (AB) resistance from ILC 3279 line into C 214 (Varshney et al, 2013c).…”
Section: Common Beanmentioning
confidence: 99%